2014
DOI: 10.1515/revce-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide-based polyampholytes and their applications

Abstract: Polyampholytes are charged macromolecules bearing both anionic and cationic groups along the polymer backbone. Polyampholytes can be synthesized by classic and controlled free radical polymerization, anionic polymerization, and group transfer polymerization (GTP). The aqueous solution behavior of polyampholytes is dictated by columbic interactions between the basic and acidic residues. Polyampholytes show both polyelectrolyte and anti-polyelectrolyte behavior in aqueous media. Factors such as charge density, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 116 publications
0
25
0
Order By: Relevance
“…In a more precise classification, if the charges are introduced by copolymerizing cationic and anionic monomers, the polymer is called amphoteric, whereas if the polymer is made of a monomer that has both cationic and anionic groups (overall zero charge), it is called zwitterionic or betaines . Comprehensive reviews on this special class of polymers can be found elsewhere . The use of polyampholyte flocculants is desired when one needs to simultaneously remove more than one contaminant with opposite charges from an effluent.…”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…In a more precise classification, if the charges are introduced by copolymerizing cationic and anionic monomers, the polymer is called amphoteric, whereas if the polymer is made of a monomer that has both cationic and anionic groups (overall zero charge), it is called zwitterionic or betaines . Comprehensive reviews on this special class of polymers can be found elsewhere . The use of polyampholyte flocculants is desired when one needs to simultaneously remove more than one contaminant with opposite charges from an effluent.…”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…Water soluble polymers are specialty chemicals with a wide range of applications in various fields for example as ion scavengers in mineral processing, as flocculants for wastewater treatment, as groundings for lacquers, as anti‐scaling agents in home care products, or as thickeners in health care products . In a large majority of these applications, the relevant physicochemical properties are mainly controlled by structural characteristics of polymers, i.e., nature, amount, and distribution of various repeat units within chains, molar mass distribution (MMD), and architecture of macromolecules (linear, branched, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…PAM is a charge-balanced polyampholyte random copolymer with high water retention ability, due to the electrostatic interactions between the electrostatic groups and water molecules, and possess an antipolyelectrolytic effect, where inclusion of salt ions in the solution causes swelling of the hydrogel instead of the collapse that occurs in ordinary polyelectrolytes. The polyampholyte and anti-polyelectrolyte effect favors their use in high electrolyte solutions due to their ability to bind to low molecular weight substances such metal ions [262].…”
Section: Polyacrylamide (Pam) and Its Derivativesmentioning
confidence: 99%